Are Financial Crises Alike? - Tang, Chrismin (IMF Working Papers; Working Paper ;, 2010)
This paper investigates whether financial crises are alike by considering whether a single modeling framework can fit multiple distinct crises in which contagion effects link markets across national borders and asset classes. The crises considered are Russia and LTCM in the second half of 1998, Brazil in early 1999, dot-com in 2000, Argentina in 2001-2005, and the recent U.S. subprime mortgage and credit crisis in 2007. Using daily stock and bond returns on emerging and developed markets from 1998 to 2007, the empirical results show that financial crises are indeed alike, as all linkages are statistically important across all crises. However, the strength of these linkages does vary across crises. Contagion channels are widespread during the Russian/LTCM crisis, are less important during subsequent crises until the subprime crisis, where again the transmission of contagion becomes rampant.